Similar Energy Expenditure During BodyPump and Heavy Load Resistance Exercise in Overweight Women - Rustaden, Anne Mette; Gjestvang, Christina; Bø, Kari; Haakstad, Lene Annette Hagen; Paulsen, Gøran (Frontiers in Physiology, 2020)
Purpose High-repetition, low-load resistance exercise in group class settings has gained popularity in recent years, with BodyPump as a prime example. For individuals using exercise for body-weight management, the energy expenditure during exercise is of interest. Therefore, we herein aimed to estimate the energy expenditure during a session of BodyPump and a time-matched session of heavy load resistance training in overweight women (BMI ≥ 25.0). Methods Eighteen women participated in the study (mean age 35.4 years ± 10.2, BMI 30.4 kg/m2 ± 4.8), 10 exercising BodyPump (50–100 repetitions each muscle group) and eight performed a heavy load session (eight repetition maximum × three sets). The energy expenditure was assessed with indirect calorimetry during the sessions and for two intervals at rest during the recovery phase: 0–20 and 120–140 min after the sessions. Results The BodyPump group lifted significantly more loads than the heavy load group (19,485 kg ± 2258 vs 15,616 kg ± 2976, p = 0.006), while energy expenditure was similar with 302 kcal ± 67 and 289 kcal ± 69 in BodyPump and heavy load group, respectively (p = 0.69). With no group differences, the resting metabolic rate (RMR) was elevated with 15–22% 2 h after exercise. Conclusion Overweight women achieved an energy expenditure of approximately 300 kcal (4.7 kcal per min) during a single session of BodyPump, which was similar with the women performing a single session of heavy load resistance exercise.